Sleep in the athlete - Day, C.; Nishino, N.; Tsukahara, Y. (Clinics in Sports Medicine, 2024)
Sleep disorders are prevalent in both the general population and athletes, but there are unique factors that athletes face due to the high-stress competitive environment.